Analysis of Credit Ratings Determinants: Evidences in Brazilian and American States - Oliveira, Nathalia Santos de; Lima, Fabiano Guasti; Bonacim, Carlos Alberto Grespan; Gatsios, Rafael Confetti; Neto, Alexandre Assaf (International Journal of Business, Economics and Management, 2020)
This piece of work, due to its relevance, aims to analyze the methodology used in the determining of ratings, not only expanding the number of variables tested and broadening the discussion on rating determinants, but also using variables which solely measure the market, liquidity credit and operational risks. Thus, the risks mentioned were compared to the ratings set for each Brazilian state from 2013 to 2017 (post-adoption of the MCASP accounting standard for financial statements) and for each American state from 2006 to 2016 (the most recently published financial datum). In face of that, this work is different from the others because it seeks to broaden the researches and the methods used in public listed companies or in financial companies, in public finances of Brazilian and American states, a subject which is little approached in researches. The ordered logit model was used since the credit rating is considered latent variables, besides following an ordinal version. The study was carried out with 50 American states, 26 Brazilian states and 648 ratings altogether. The model proposed in this work proved to be efficient, being able to successfully estimate 64.10% of the sample of the Brazilian states and 68.50% of the sample of the American states. The results reached are specially relevant for stakeholders, who are able to analyze or manage their possible investments regarding risk and return.